Connexin 43 Channels Are Essential for Normal Bone Structure and Osteocyte Viability. (16th February 2015) - Xu, Huiyun; Gu, Sumin; Riquelme, Manuel A; Burra, Sirisha; Callaway, Danielle; Cheng, Hongyun; Guda, Teja; Schmitz, James; Fajardo, Roberto J; Werner, Sherry L; Zhao, Hong; Shang, Peng; et al.
ABSTRACT: Connexin (Cx) 43 serves important roles in bone function and development. Targeted deletion of Cx43 in osteoblasts or osteocytes leads to increased osteocyte apoptosis, osteoclast recruitment, and reduced biomechanical properties. Cx43 forms both gap junction channels and hemichannels, which mediate the communication between adjacent cells or between cell and extracellular environments, respectively. Two transgenic mouse models driven by a DMP1 promoter with the overexpression of dominant negative Cx43 mutants were generated to dissect the functional contribution of Cx43 gap junction channels and hemichannels in osteocytes. The R76W mutant blocks the gap junction channel, but not the hemichannel function, and the Δ130‐136 mutant inhibits activity of both types of channels. Δ130‐136 mice showed a significant increase in bone mineral density compared to wild‐type (WT) and R76W mice. Micro–computed tomography (µCT) analyses revealed a significant increase in total tissue and bone area in midshaft cortical bone of Δ130‐136 mice. The bone marrow cavity was expanded, whereas the cortical thickness was increased and associated with increased bone formation along the periosteal area. However, there is no significant alteration in the structure of trabecular bone. Histologic sections of the midshaft showed increased apoptotic osteocytes in Δ130‐136, but not in WT and R76W, mice which correlated with altered biomechanical and estimated bone material properties. Osteoclasts were increased along the endocortical surface in both transgenic mice with a greater effect in Δ130‐136 mice that likely contributed to the increased marrow cavity. Interestingly, the overall expression of serum bone formation and resorption markers were higher in R76W mice. These findings suggest that osteocytic Cx43 channels play distinctive roles in the bone; hemichannels play a dominant role in regulating osteocyte survival, endocortical bone resorption, and periosteal apposition, and gap junction communication is involved in the process of bone remodeling. © 2014 American Society for Bone and Mineral Research.